2016
DOI: 10.1109/tsg.2015.2445794
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Real-Time Power Balancing in Renewable-Integrated Power Grids With Storage and Flexible Loads

Abstract: Abstract-The large-scale integration of renewable generation directly affects the reliability of power grids. We investigate the problem of power balancing in a general renewable-integrated power grid with storage and flexible loads. We consider a power grid that is supplied by one conventional generator (CG) and multiple renewable generators (RGs) each co-located with storage, and is connected with external markets. An aggregator operates the power grid to maintain power balance between supply and demand. Aim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 29 publications
0
65
0
Order By: Relevance
“…In our previous studies, we have shown that PLLA-containing block copolymers can be fabricated using a combination of reversible addition-fragmentation chain transfer (RAFT) and ring-opening polymerisation (ROP), where we have been able to achieve tuneable cylindrical micelles with a range of coronal blocks by CDSA. [27][28][29] Further work was carried out to enrich the functionality of the PLLA-based cylinders 30,31 and successfully realize stereocomplexation-triggered morphological transitions, 32 indicating the promising future of these cylindrical particles in the biomedical realm. Similar to conventional phase separation-driven assembly, it can be expected that triblock copolymers will lead to an alternate morphology when undergoing CDSA as a consequence of the extra coil phase.…”
mentioning
confidence: 99%
“…In our previous studies, we have shown that PLLA-containing block copolymers can be fabricated using a combination of reversible addition-fragmentation chain transfer (RAFT) and ring-opening polymerisation (ROP), where we have been able to achieve tuneable cylindrical micelles with a range of coronal blocks by CDSA. [27][28][29] Further work was carried out to enrich the functionality of the PLLA-based cylinders 30,31 and successfully realize stereocomplexation-triggered morphological transitions, 32 indicating the promising future of these cylindrical particles in the biomedical realm. Similar to conventional phase separation-driven assembly, it can be expected that triblock copolymers will lead to an alternate morphology when undergoing CDSA as a consequence of the extra coil phase.…”
mentioning
confidence: 99%
“…Energy storage has been considered at the power grid operator or aggregator to combat the fluctuation of renewable generation, with many works in literature on storage control and assessment of its role in renewable generation [2], for power balancing with fixed load [3], [4] or flexible load control [6], [7], and for phase balancing [5]. Residential energy storage systems to reduce electricity cost have been considered without renewable [17] and with renewable integration [10]- [13], [18]- [24].…”
Section: A Related Workmentioning
confidence: 99%
“…To minimize the objective of P4 b , one possible solution is to minimize E w t and maximize F w s,t . Due to constraint (6), S w c,t · F w s,t = 0 must be satisfied. Thus, we have two conditions: i) If F w s,t ≥ 0 and S w c,t = 0, it means the remaining amount S t − S w,t , if any, will be only sold back to the grid.…”
Section: Appendix D Proof Of Propositionmentioning
confidence: 99%
“…The work in [6] investigates the reduction in different conventional generators' ramping activity by increasing ramping capability of storage systems. In [7], it is concluded that larger storage facilities lead to less ramping constraints and thus, reduction of the total system cost. In [8], dispatching storage systems to mitigate forecast errors of wind power production is discussed considering the ramping capabilities of storage facilities.…”
Section: Introductionmentioning
confidence: 99%